PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA BAGI HASIL, DAN JUMLAH PENDUDUK TERHADAP TINGKAT KEMISKINAN DENGAN BELANJA DAERAH SEBAGAI VARIABEL INTERVENING PADA KABUPATEN/ KOTA DI PROVINSI RIAU TAHUN 2011 S.D 2015 - Riry Isramiwarti; M. Rasuli; Taufeni Taufik (PEKBIS, 2017)
The purpose of this research is to know the influence of Local Revenue (PAD),General Allocation Fund (DAU), DBH and Total Population to Poverty Level throughRegional Expenditure at Regency / City in Riau Province Year 2011-2015. The studywas conducted for 2 months, from October to December 2016. The object of thisstudy is the district / city in Riau Province, the population and sample used in thisstudy are 12 districts / municipalities in Riau Province. The data used are secondarydata obtained based on documentation of result from publication of BPS (CentralBureau of Statistics) for data of Economic Growth and Poverty Rate while data ofPendapatan Asli Daerah (PAD), General Allocation Fund (DAU), DBH and CapitalExpenditure Obtained from the Financial Management Agency and Regional Asset(BPKAD) Riau Province. The analysis tool used is Path Analysis using Partial LeastSquare (PLS) method. The result of the research shows that Pendapatan AsliDaerah (PAD), Profit Sharing Fund (DBH) and Total Population (JP) have asignificant influence to the decreasing of Poverty Level through RegionalExpenditure (BD). While the General Allocation Fund (DAU) does not have asignificant effect on the decrease of the number of Poverty Rate through RegionalExpenditure (BD). Regional Expenditure (BD) as an intervening variable has animportant role in increasing the influence of Pendapatan Asli Daerah (PAD) and thePopulation (JP) in reducing Poverty, but has little role in increasing the effect ofGeneral Allocation Fund (DAU) and Revenue Sharing Fund (DBH) to reducePoverty Rate.